Filemon mamon A book in two languages - Bellen, Christine S. 1973- (Adarna House, 2017)
The travails of an overweight child are playfully portrayed in this humorous and witty story. His name says it all -- a taunt in itself! But Filemon cares enough about playing a hero on stage someday that he is willing to mend his ways. Without anyone realizing it, the story has become an amusing lesson on healthy eating!